Tools for coordinating measurement use in science education and training - Fátima Sancheznieto; Christine M. Pribbenow; Christine Pfund (Journal of Microbiology & Biology Education)
ABSTRACT The improvement of existing science education interventions and the development of new ones requires cohesive, large-scale evaluation and testing that inform what works, for whom, and in what context. Systems approaches to design, implement, and evaluate interventions require knowledge, skills, and expertise in studying humans alongside the lived experiences and positionality of biological science leaders and practitioners who may not have the necessary social science background to do so. Developing a shared understanding of evaluation design and measurement use is an important component toward fostering interdisciplinary collaboration for the improvement of our education and training interventions. In this perspective, we argue that the coordinated use of common measures benefits individual interventions, as well as consortia and collaborative groups that make use of them. We provide examples of consortia and partnerships that make use of common measures within and across programs for evaluation and research. We then describe existing common measure tools and libraries that foster the coordination of common measures. Finally, we suggest next steps to improve tools for use by the broader science education and training research community.